A sacred bridge or an unsteady pontoon? - Bujić, Bojan (Muzikološki zbornik, 2007)
Philosophical discussion of music based on the principle that music is a form of language, encounters difficulties. Some aspects of music do tend towards language-like structures, while others pull away from them. If only the language model is upheld, then philosophical theories assume a prescriptive character, aiming to establish in an a priori manner which music has meaning (hence value) and which not. This problem is particularly acute in the Anglo-American tradition of anaytical philosophy.
Keywords: estetika glasbe; filozofija; glasba; jezik; Language; linguistics; lingvistika; music; narativnost; philosophy